How do national university science parks influence corporate green innovation? Evidence from Chinese listed companies - Yue Zhang; Shijie Ding (Quantitative Finance and Economics)
As a cooperative platform connecting universities, enterprises, and the government, national university science parks (NUSPs) have a major impact on promoting technological innovation and industrial transfer and are a key component of higher education reform and innovation-driven development strategy in China. This study utilized panel data from Chinese listed firms from 2000 to 2020 and employed a difference-in-differences approach to evaluate the impact of NUSPs, initiated by the Chinese government in 2002, on corporate green innovation. The results show that NUSPs significantly enhance corporate green innovation performance. Specifically, channels such as research and development (R&D) investment, technical talent, and alleviation of financial constraints contribute to this stimulation. The moderating analysis reveals that the positive effect of NUSP projects on corporate green innovation is more pronounced in nonstate-owned and labor-intensive firms, as well as in non-heavy polluting industries, high-tech and technology-intensive enterprises. The heterogeneity analysis indicates that NUSPs have a comparatively notable positive influence on the green innovation level of enterprises that rely on double first-class universities, have government R&D subsidies, and are subject to relatively high regional environmental supervision intensity. Theoretically, it enriches the exploration of the correlation between NUSPs and corporate green innovation, reveals its internal influence mechanism, and broadens the research vista in the field of university-industry interactive innovation. Practically, it guides government policymaking to support parks and enterprise decisions to cooperate for enhanced green innovation and sustainable development, promoting industry-academia-research integration and a good innovation ecosystem.